1996
DOI: 10.1139/b96-137
|View full text |Cite
|
Sign up to set email alerts
|

La relation entre le Striga hermonthica et ses hôtes: une synthèse

Abstract: R&sumC : La mauvaise herbe parasite Striga hermonthica inflige des pertes de rendement considCrables au mais, au mil et au sorgho en Afrique. L'importance des dommages subis par les cultures est liCe B leur interaction Ctroite avec le parasite. La graine de S. hermonthica germe en rCponse B des stimulants de germination exsudCs par les racines de cCrCales. L'extrCmitC de la radicule se differencie ensuite en un haustorium qui s'attache B une racine de l'hate et pCnbtre ses tissus. Une connexion est alors Ctabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 144 publications
(145 reference statements)
0
1
1
2
Order By: Relevance
“…The observed average yield gain of 3.2% yr −1 under Striga infestation in our study was greater than the gains reported for 50 early-and 56 extra-early-maturing openpollinated maize varieties (Badu-Apraku et al, 2013. This yield gain was accompanied by marked decrease in both parasite damage and emergence, leading to more dry matter accumulation in the resistant hybrids through a minimal rate of nutrient transfer from the host to the parasite and maintenance of higher rates of photosynthesis and metabolism under parasite pressure (Gurney et al, 1995;Olivier, 1996;Gurney et al, 2002). In a study on rice (Oryza sativa L.), Cissoko et al (2011) found negative correlation between aboveground biomass of the cultivars and the amount of parasite biomass measured on their roots, highlighting the potential that exists to further reduce parasite damage and emergence for attaining much greater productivity gains in maize hybrids targeted to areas infested with S. hermonthica.…”
Section: Discussioncontrasting
confidence: 63%
“…The observed average yield gain of 3.2% yr −1 under Striga infestation in our study was greater than the gains reported for 50 early-and 56 extra-early-maturing openpollinated maize varieties (Badu-Apraku et al, 2013. This yield gain was accompanied by marked decrease in both parasite damage and emergence, leading to more dry matter accumulation in the resistant hybrids through a minimal rate of nutrient transfer from the host to the parasite and maintenance of higher rates of photosynthesis and metabolism under parasite pressure (Gurney et al, 1995;Olivier, 1996;Gurney et al, 2002). In a study on rice (Oryza sativa L.), Cissoko et al (2011) found negative correlation between aboveground biomass of the cultivars and the amount of parasite biomass measured on their roots, highlighting the potential that exists to further reduce parasite damage and emergence for attaining much greater productivity gains in maize hybrids targeted to areas infested with S. hermonthica.…”
Section: Discussioncontrasting
confidence: 63%
“…Since syringic acid is an ubiquitous metabolite of lignin biosynthesis and peroxidase reactions are involved in most pathogenic processes, a 2,6dimethoxy-parabenzoquinone is probably produced by all host plants. Soil inundation with microbes that destroy striga seeds Fusarium species Smicronyx species a Source: Doggett (1988), Carson (1988), Obilana (1990), Dembe Âle  and Konate  (1991), Babiker et al (1993), Berner et al (1994Berner et al ( , 1996aBerner et al ( , 1997a, Carsky et al (1994), Odhiambo and Ransom (1994), Olivier (1995Olivier ( , 1996, Gressel et al (1996), Hoffmann et al (1997, Abayo et al (1998), Kroschel (1998), Salle  (1998.…”
Section: Resistance Mechanismsmentioning
confidence: 99%
“…Dans le même ordre d'idée, l'identification des arbres résistants nous paraît une voie prospectable. Chez les céréales, l'existence de différences de sensibilité de plusieurs cultivars de sorgho au Striga hermonthica a été mise en évidence (DOGGET 1952, 1965, LAST 1960ain OLIVIER 1996. Chez le peuplier, HARIRI (1989) et HARIRI et al (1990 rapportent l'existence de cultivars résistants au gui.…”
Section: Résistance Variétaleunclassified
“…Les Loranthaceae causent d'importants dégâts dans les formations naturelles et les plantations de nombreux pays africains : Burkina Faso, Cameroun, Côte d'Ivoire, Gabon, Ghana, Mali, Nigeria, Ouganda (ROOM 1970, CLERK 1978, BOUSSIM 1991, BOUSSIM et al 1993aet 1993b, BOUSSIM 2002, TRAORÉ 1994, TRAORÉ & DA 1995, 1996et 1997, GUYOT & NTAWANGA OMANDA 1998) et du monde. Les dégâts, difficiles à évaluer, posent parfois un problème majeur dans la sylviculture.…”
Section: Introductionunclassified